ADAPTATION TEACHER AND HOUSEWIFE FOR CREATING STUDENT RESILIENCE AMID COVID-19 - Bahagia - Bahagia; De Ajeng Ayu Priatna; Fachruddin Majeri Mangunjaya; Rimun Wibowo (GEOGRAPHY : Jurnal Kajian, Penelitian dan Pengembangan Pendidikan, 2021)
The purpose of this research is to investigate the adaptation of teacher and housewife for creating student resilience. The research method uses an ethnographic qualitative approach. In order to gather data was used an in-depth interview. The result is probed meticulously through triangulation technique and triangulation sources. The result shows that pandemic COVID 19 have an adverse impact to housewife. Another impact is the student experience boring through online learning. On the contrary, there are some merits about online learning such as parents can supervise their children both the pattern of eating behavior as well as strengthen togetherness in family. The other finding is teacher conduct some strategy for coping pandemic including teacher release home visit to the student house. Besides that, the teacher has distorted learning face to face to daring system to ensure that learning activity can be implied amid pandemic. It must be encouraged by modification of material teaching through inventing video learning to make it more convenient to children. In addition, housewife applicate some strategy for overcoming this obstacle such as they don’t compel learning to children but they accompany the children for playing with them. Then, the housewife has bolstered the children like giving nutrient balance.